Perencanaan Pemasangan Medium Approach Lighting System (MALS) pada Runway 09 di Bandar Udara I Gusti Ngurah Rai - Bali - Wijaya, Dukhan Firman Hakim; Bunahri, Rifqi Raza; Kona, Musri (SKY EAST: Education of Aviation Science and Technology, 2023)
Currently, I Gusti Ngurah Rai International Airport Bali is equipped with a runway 3000 meters long and 45 meters wide which is equipped with an Airfield lighting System (ALS) such as Runway Edge Light, Threshold/Runway end Light, Taxiway Edge Light, Precision Approach Path Indicator (PAPI), and Approach Light as visual landing aids in bad weather conditions or at night. On Runway 27 PALS Category I is installed for 900 meters and a complete Sequence Flashing Light from the first bar to the last bar, however on Runway 09 only a Runway Threshold Indicator Light (RTIL) is installed without an Approach Light. If a pilot wants to land his plane using Runway 09 then the plane only gets the Runway Threshold Indicator Light (RTIL) as a visual landing aid when approaching Threshold, in reality a pilot needs a precise visual reference to approach the runway. In this article, the author uses qualitative research. This research was conducted using field observation methods, located at I Gusti Ngurah Rai International Airport, Bali. So the results obtained are that Bali's I Gusti Ngurah Rai Airport does not have approach lights on runway 09 because it does not have land that allows PALS Category I to be installed there. The Airfield Lighting System at I Gusti Ngurah Rai Airport in Bali is in accordance with the standards contained in Kp 326 of 2019 concerning Standards and Operations of Civil Aviation Safety Regulations (Casr Manual of Standards - Part 139) and SKEP 114 of 2002 concerning Standards for Lighting System Installation Drawings Airport (Airfield Lighting System).